ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Dinas Sosial Tenaga Kerja Dan Transmigrasi Kabupaten Mamuju Utara) - Makkaratte, Andi Muh. Wahyuddin (Katalogis, 2017)
The purpose of this research is to test and analyze the influence of leadership style and work motivation on employees performance (Study on the employees of Badan Kesbangpol dan Linmas Provinsi Jawa Tengah). The sample used in this research consists of 60 respondents from 106 employees. The method of sampling used is by purposive sampling, method data analysis used are multiple linear regression analysis. Based on the results of data analysis, the regression equations obtained are as follows: Y = 0,465 X 1 + 0,398 X 2. The result of the reseacrh using t test that leadership style and work motivation have positive significant influence to employees performance. The result of the research simultantly using F test, shows that all of the independent variables influence significant to employees performance. The coefficient determinant (R 2 ) is 0.680 which means 68% employees performance variation explained by independent variables, where as 32% explained by another variables which is not followed.